Dyadic assessment of perceived partner forgiveness and relationship ınvestment model in turkish romantic couples - Esra EKER DURMUŞ; Yaşar ÖZBAY; Durmuş, Esra Eker (My University, 2023)
The aim of this study is to investigate the relationship between perceived partner forgiveness and relationship investment variables [relationship satisfaction, quality of alternatives, investment size,] in dyadic context. The data were collected from 116 heterosexual romantic couples (n = 232) in the 18-30 age group having at least six months of romantic relationship. This study employed cross-sectional correlational study design. Actor-Partner Interdependence Model (APIM) was used to examine the predictive effect of independent variables of the couples on their dependent variables (actor) and their partners’ dependent variables (partner). In this study, dependent variables are relationship satisfaction, quality of alternatives and investment size, independent variable is subjective partner forgiveness. Subjective Partner Forgiveness Scale, The Investment Model Scale were used for data collection. The results suggest that as the level of forgiveness experienced by men and women increase relationship satisfaction increases in the relations between relationship satisfaction and perceived partner forgiveness. Results of the quality of the options and perceived partner forgiveness indicate that the partners' assessment of the quality of alternative decrease as the perceived forgiveness level of both men and women increase. Results of relationship investment and perceived partner forgiveness indicate that the partners' assessment of relationship investment increases as perceived forgiveness in women and men increase. The results were discussed in the context of relevant literature.
Keywords: perceived forgiveness; forgiveness; relationship investment